2011
DOI: 10.1182/blood-2011-02-335539
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of genes encoding PU.1 and Spi-B in B cells impairs differentiation and induces pre-B cell acute lymphoblastic leukemia

Abstract: The E26 transformation-specific (Ets) transcription factor PU.1 is required to generate lymphoid progenitor cells from hematopoietic stem cells, but it is not required to generate B cells from committed B-cell lineage progenitors. We hypothesized that PU.1 function in B-cell differentiation is complemented by the related Ets transcription factor Spi-B. To test this hypothesis, mice were generated lacking both PU. IntroductionThe E26 transformation-specific (Ets) transcription factor PU.1 (encoded by the gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 37 publications
6
73
0
Order By: Relevance
“…4B). SPIB and SPI1 have the same canonical motif (PU.1) and are both essential for B cell development (Sokalski et al 2011). (2) GATA1 was the most frequently discovered noncanonical motif in K562 cells.…”
Section: Cell-type-specific Binding Of Sequence-specific Tfsmentioning
confidence: 99%
“…4B). SPIB and SPI1 have the same canonical motif (PU.1) and are both essential for B cell development (Sokalski et al 2011). (2) GATA1 was the most frequently discovered noncanonical motif in K562 cells.…”
Section: Cell-type-specific Binding Of Sequence-specific Tfsmentioning
confidence: 99%
“…We previously noted that levels of Blnk mRNA transcripts were reduced in sorted splenic DPB B-ALL cells compared with control B cells (15). Therefore, we hypothesized that Blnk is a target of transcriptional activation by PU.1 and/or Spi-B.…”
mentioning
confidence: 99%
“…Reduced Spi-B expression was recently associated with human B-ALL (14). Our laboratory previously showed that mice that lack both PU.1 and Spi-B in the B cell lineage (CD19 +/Cre Sfpi1 lox/lox Spib 2/2 mice, henceforth known as DPB mice) have impaired B cell development and develop B-ALL with 100% incidence rate by 21 wk of age (15). These results demonstrate that PU.1 and Spi-B have tumorsuppressor function in the B cell lineage and suggest that mutation of the SPI1 and SPIB genes, or upstream activators of these genes, could be oncogenic drivers in leukemia-initiating cells.…”
mentioning
confidence: 99%
“…On the other hand, RUNX1 is downregulated or mutated in TLX1 T-ALL, as its normal expression entails tumorsuppressing effects [92]. Conversely, the role of PU.1 in ALL is less established, although it is expressed in most B-ALLs, and that its deletion together with SpiB systematically results in leukemia [93,94]. In T-ALL recent studies have reported expression of PU.1; however, the mechanisms in which it could contribute towards leukemogenesis remain unclear [93,95].…”
Section: Runx1 and Pu1 In T And B-cellsmentioning
confidence: 99%